Differences in Skipper Leadership Type with Vessel Health Risk Level at Tanjung Perak Harbour Surabaya-East Java - Nero, Tonny; Mindiharto, Sestiono; Inayah, Zufra; Has, Dwi Faqihatus Syarifah (Ahmar Metastasis Health Journal, 2024)
The presence of cockroach and rat vectors on ships is an indication of the crew's lack of attention to ship health efforts. The purpose of this study was to analyze the difference between the skipper's leadership type and the level of ship health risk in Tanjung Perak Port, Surabaya, East Java. The research design was a cross-sectional survey with an observation approach. The population was all crew members of 1,164 domestic ship arrivals at Tanjung Perak Port Surabaya-East Java in March 2023 totaling 23,073 crew members. The sample size of 298 respondents was taken with Simple Random Sampling. The instruments used were a questionnaire sheet about the skipper's leadership a supervision checklist sheet for vector inspection and BPP about the level of ship health risk. Analysis with Fisher's Exact Test. The results showed that the skipper's leadership type was mostly democratic, namely 223 people or 74.8%. The level of ship health risk is almost absent of public health risk factors, namely 280 ships or 94.0%. Fisher's Exact Test showed p=0.000<0.05. The conclusion is that there is a difference between the skipper's leadership type and the level of ship health risk. The interests of the crew by trying to create a more open relationship can increase and maximise the implementation of ship sanitation. Further research by examining other factors related to the level of ship health risks that have not been studied in this study accompanied by in-depth interviews with all crew members so that the research results are more objective.